Survey of the status and distribution of primates in Togo (West Africa). Issue 4 (2nd October 2017) - Segniagbeto, Gabriel Hoinsoudé; Assou, Delagnon; Koda, Koudzo D.; Agbessi, Eric Koffi G.; Atsri, Komina H.; Dendi, Daniele; Luiselli, Luca; Decher, Jan; Mittermeier, Russell A.
Abstract: The distribution of West African primates is still poorly explored in Togo. Field data on distribution, abundance (kilometric index of abundance) and characteristics of primate habitat at six protected and unprotected areas of Togo are reported in this paper. Eight species and 831 primate individuals were visually recorded during field surveys. A few other species were suspected, but not recorded. Species directly observed in the field during our surveys were Cercopithecus erythrogaster erythrogaster, Cercopithecus petaurista petaurista, Cercopithecus mona, Chlorocebus tantalus, Colobus vellerosus, Erythrocebus patas, Papio anubis and Galago senegalensis . Our surveys did not provide any evidence of the persistence of the chimpanzee ( Pan troglodytes verus ) in the country. Most of the Togolese primates are of low conservation concern according to The International Union for the Conservation of Nature (IUCN). However, our surveys suggested that the status of most of the species in Togo is instead 'threatened'. Fazao Malfakassa and Togodo National Parks appeared to be the most relevant areas for primates in terms of their species diversity and relative density, and also the most promising sites for developing primate-oriented ecotourism strategies in Togo.